2019
DOI: 10.1002/cplu.201900151
|View full text |Cite
|
Sign up to set email alerts
|

A One‐Step Chemical Strategy for the Formation of Carbon Nanotube Junctions in Aqueous Solution: Reaction of DNA‐Wrapped Carbon Nanotubes with Diazonium Salts

Abstract: A single‐step chemical strategy allows the formation of single‐walled carbon nanotube (SWCNT) molecular junctions in aqueous solution. SWCNTs were first wrapped with DNA to be water soluble and solution processable. Diazonium salts, which have been shown to react spontaneously with carbon nanotubes in water at room temperature, were then employed to covalently link SWCNT segments. The DNA wrapping of the nanotubes acted as a protective layer that limits the functionalization predominantly to the nanotube termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
1
5
0
2
Order By: Relevance
“…In recent years, environmental awareness has fostered increasing interest in the development of green production methods for carbon nanostructures [24] and their functionalization with virtually zero waste generation [25]. Diazonium salts have been proposed as covalent linkers for the tips of SWCNTs that were previously wrapped in DNA to protect the sidewalls from undesired functionalization, thus enabling the preferential crosslinking of the CNT ends in water and at room temperature [26]. Environmentally-friendly carbon sources, such as vegetable oils, have also been used to produce b-CNTs [27].…”
Section: Experimental Studies and Branched Cns Productionmentioning
confidence: 99%
“…In recent years, environmental awareness has fostered increasing interest in the development of green production methods for carbon nanostructures [24] and their functionalization with virtually zero waste generation [25]. Diazonium salts have been proposed as covalent linkers for the tips of SWCNTs that were previously wrapped in DNA to protect the sidewalls from undesired functionalization, thus enabling the preferential crosslinking of the CNT ends in water and at room temperature [26]. Environmentally-friendly carbon sources, such as vegetable oils, have also been used to produce b-CNTs [27].…”
Section: Experimental Studies and Branched Cns Productionmentioning
confidence: 99%
“…In den letzten Jahren wurde über eine Reihe verschiedener Sauerstoff‐ und Aryl‐Defekte berichtet, die nun sehr vielversprechende Werkzeuge für die Erzeugung von helleren/modifizierten SWCNTs, pH‐ or Saccharid‐Sensoren, kurzen fluoreszierenden SWCNTs für die hochauflösende Mikroskopie oder Einzelphotonenquellen für das Quanten‐Computing sind . Darüber hinaus verschiebt dieses neue Defekt‐induzierte Fluoreszenzsignal die Emission noch weiter in das Biotransparenzfenster, was zu noch besseren Gewebepenetrationseigenschaften führt …”
Section: Einführungunclassified
“…[30] Diese Technik ermçglichte auch die Abstimmung der Defektfluoreszenz sowohl in Bezug auf die Intensitäta ls auch auf die Emissionswellenlänge über verschiedene Substituenten am Aryl/Alkyl-Defekt. [31][32][33][34] In den letzten Jahren wurde über eine Reihe verschiedener Sauerstoff-und Aryl-Defekte berichtet, die nun sehr vielversprechende Werkzeuge fürd ie Erzeugung von helleren/modifizierten SWCNTs, [31,35,36] pH- [37] or Saccharid [38] -Sensoren, kurzen fluoreszierenden SWCNTs fürd ie hochauflçsende Mikroskopie [39] oder Einzelphotonenquellen für das Quanten-Computing sind. [40,41] Darüber hinaus verschiebt dieses neue Defekt-induzierte Fluoreszenzsignal die Emission noch weiter in das Biotransparenzfenster,w as zu noch besseren Gewebepenetrationseigenschaften führt.…”
Section: Einführungunclassified
“…In the last years, a number of different oxygen and aryl defects were reported that are now very promising tools for the generation of brighter/modified SWCNTs, pH and saccharide sensors, short fluorescent SWCNTs for superresolution microscopy, and single‐photon sources for quantum computing . Furthermore, this new defect‐induced fluorescence feature moves the emission even further into the biotransparency window, leading to even better tissue penetration properties …”
Section: Introductionmentioning
confidence: 99%
“…[30] This technique also enabled tuning of the defect fluorescence both in terms of intensity and emission wavelength via different substituents on the aryl/alkyl defect. [31][32][33][34] In the last years,an umber of different oxygen and aryl defects were reported that are now very promising tools for the generation of brighter/modified SWCNTs, [31,35,36] pH [37] and saccharide [38] sensors,s hort fluorescent SWCNTs for superresolution microscopy, [39] and single-photon sources for quantum computing. [40,41] Furthermore,t his new defect-induced fluorescence feature moves the emission even further into the biotransparencywindow,leading to even better tissue penetration properties.…”
Section: Introductionmentioning
confidence: 99%